ALTRUISTIC AND AGGRESSIVE TYPES OF BEHAVIOR IN A NON-ANTAGONISTIC DIFFERENTIAL GAME - Anatolii F. Kleimenov (Ural Mathematical Journal, 2018)
An example of a non-antagonistic positional (feedback) differential two-person game (NPDG) is considered in which each of two players, in addition to the normal type of behavior, oriented toward maximizing own functional, can use other types of behavior. In particular, it can be altruistic and aggressive types. In the course of the game players can switch their behavior from one type to other. The use by players of types of behavior other than normal can lead to outcomes more preferable for them than in a game with only normal behavior. The example with the dynamics of simple motion on a plane and phase constraints illustrates the procedure of constructing new solutions.